2008
DOI: 10.1007/s10808-008-0092-5
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries and exact solutions of the shallow water equations for a two-dimensional shear flow

Abstract: This paper considers nonlinear equations describing the propagation of long waves in two-dimensional shear flow of a heavy ideal incompressible fluid with a free boundary. A nine-dimensional group of transformations admitted by the equations of motion is found by symmetry methods. Twodimensional subgroups are used to find simpler integrodifferential submodels which define classes of exact solutions, some of which are integrated. New steady-state and unsteady rotationally symmetric solutions with a nontrivial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 8 publications
(11 reference statements)
0
28
0
Order By: Relevance
“…Such very important problems as well-posedness and nonlinear stability of the Benney-type model obtained by the Heaviside closure were investigated in [21,22]. Another paper [23] was dedicated to the investigation of the Benney system (1.3) from the Lie group analysis. Interesting classes of particular solutions were found in this paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such very important problems as well-posedness and nonlinear stability of the Benney-type model obtained by the Heaviside closure were investigated in [21,22]. Another paper [23] was dedicated to the investigation of the Benney system (1.3) from the Lie group analysis. Interesting classes of particular solutions were found in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…The author thanks Alexander Chesnokov, Sergey Gavrilyuk, Oleg Mokhov, Vladimir Taranov, Sergey Tsarev and Victor Vedenyapin for their stimulating and clarifying discussions. In addition, the author expresses his gratitude to both anonymous referees, who pointed out the results obtained by other researchers working in the same field (see [15,[21][22][23][24]) and who improved the quality and clarity of this paper. …”
mentioning
confidence: 76%
“…In the present paper, we describe sound characteristics on the equilibrium state and study stationary simple waves of system (1.1). We also note papers [3,4], in which the group properties of some models of atmospheric physics are studied and exact solutions constructed using the symmetry groups admitted by these models are studied.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…There are various applications of the Lie point symmetries in physical theories 15‐22 as also in fluid dynamics and in shallow‐water equations. The Lie point symmetries of the nonrotating shallow‐water equations were studied in Chesnokov, 23 while a similar analysis with specific Coriolis term was performed in Chesnokov 24 . In the latter case, it was found that the special Coriolis term can be neglected by the field equations with the use of point transformations.…”
Section: Introductionmentioning
confidence: 99%